Corneal Endothelial Cell Proliferation: A Function of Cell Density - Patel, Sangita P. (2009)
PURPOSE: To determine how stimuli that increase corneal endothelial cell proliferation of human corneas in culture relate to changes in endothelial cell density in the central and peripheral cornea. METHODS: Human donor cadaver corneas not suitable for transplantation were divided into four pie-shaped wedges and incubated at 37°C in medium supplemented with fetal bovine serum, epidermal growth factor, fibroblast growth factor, and gentamicin. To promote a proliferative response, samples were treated with EDTA at concentrations of 0, 0.5, 2.5, and 5.0 mM for 1 hour and then returned to culture medium. Endothelial cell proliferation was assayed with Ki-67 immunolocalization 48 and 96 hours after EDTA treatment. Samples were mounted with propidium iodide or DAPI. The total number of cells and the number of Ki-67–positive cells were counted in three regions, defined as central, mid, and peripheral cornea, to determine endothelial cell density and percentage of proliferation. RESULTS: A proliferative response to EDTA was not found. However, increased proliferation was noted in the central compared with the peripheral corneal region. Unexpectedly, the increased proliferation in the central region corresponded to a trend of lower endothelial cell density in the central region compared with the peripheral region. Corneal endothelial cell proliferation under our culture conditions is noted primarily when cell density is less than 2000 cells/mm(2). CONCLUSIONS: Corneal endothelial cell proliferation under our culture conditions does not lead to supranormal endothelial cell density. Rather, cell proliferation is noted in those regions that may be experiencing a greater burden of cell loss.